Status Epilepticus A Clinical Perspective (Current Clinical Neurology, 2018)
This expanded edition represents the state of the art and captures many changes in our understanding of status epilepticus over the past decade. Varied characteristics and treatment approaches, the growing use of continuous EEG monitoring, and insights into the underlying biology and pathophysiology of convulsive and nonconvulsive SE are covered in depth. Authored by leading neurologists, epileptologists, and clinical neurophysiologists from around the world, this volume prepares the clinician to confront these multifaceted, sometimes subtle, and occasionally life-threatening conditions.